Yellow Triazine as an Efficient Photoinitiator for Polymerization and 3D Printing under LEDs. Issue 18 (27th August 2019) - Lai, Haiwang; Zhu, Di; Xiao, Pu
Abstract: The search for new efficient photoinitiators for polymerization under the illumination of visible light is under extensive investigation due to their wide application in 3D printing. 2‐(4‐Methoxystyryl)‐4, 6‐bis(trichloromethyl)‐1, 3, 5‐triazine (yellow triazine, R‐Cl) alone or the R‐Cl/additive systems have been indicated as promising photoinitiating systems in the free radical polymerization at 405 nm in our previous study. Here, further investigation of R‐Cl in the polymerization of a series of difunctional (meth)acrylate monomers is described. The effect of monomers on the polymerization performance is elucidated. The interplay of functional group, double bond concentration, and fluidity determines the polymerization rate and final conversions. Remarkably, R‐Cl shows better photoinitiating ability than well‐known commercial photoinitiator bisacylphosphine oxide in the polymerization of bis‐GMA/TEGDMA blend and EB605 under LED at 400 nm. The optimum concentrations of R‐Cl in the photopolymerization of TetEGDA and DPGDA monomers are revealed, the results of which are used to guide the 3D printing of DPGDA. Abstract : The effects of monomer property and concentration of photoinitiators on the photopolymerization performance initiated by 2‐(4‐methoxystyryl)‐4, 6‐bis(trichloromethyl)‐1, 3, 5‐triazine (yellow triazine) under LED irradiation are investigated. The potent initiating efficiency of yellow triazine allows a low dosage (0.1 wt%) to be used for efficient 3D printing of di(propylene glycol) diacrylate (DPGDA) under 405 nm irradiation.